The spindle checkpoint - Hardwick, Kevin (Henry Stewart Talks, 2009)
Cell cycle checkpoints, The metaphase to anaphase transition, The spindle checkpoint, What do cells monitor?, Unattached kinetochores, Lack of tension, Checkpoint components, Budding yeast genetic screens, Microcolony assay, Localisation of Mad proteins, Checkpoint proteins are all recruited kinetochores, Role of kinetochores, Global signaling, Identification of Cdc20 as the checkpoint effector, CdC20-APC, FRAP, Mad1/Mad2 complex as a template, The anaphase promoting complex (APC), How is anaphase onset inhibited, Mad2 and Mad3 bind mitotic APC, Separase regulation by securin, Error correction, Chromosomal passenger proteins, How to sense a lack of tension?, Checkpoint role(s) of Aurora kinase (Ipl1), Checkpoint silencing, Disease relevance, Future directions